2014
DOI: 10.1186/1745-6215-15-362
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of the reporting of continuous outcome measures and clinical significance of results in randomized trials of non-pharmacological interventions

Abstract: BackgroundReporting the scoring details of continuous outcome measures in randomized trials allows readers to interpret the size of any effect of the intervention. This study aimed to determine, in a sample of randomized trials: 1) the completeness of reporting of scoring details for continuous outcome measures, and 2) whether trial authors comment on the clinical significance of statistically significant trial results.MethodsA descriptive analysis of randomized trials of non-pharmacological interventions publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Our results are coherent with the literature where the reporting of results in terms of clinical relevance is sparsely used across trials [1]. We confirm the preliminary results published by Van Tulder et al focused on exercise therapy for chronic LBP reporting that less than half of studies (39%) with positive conclusions shown clinically important differences [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are coherent with the literature where the reporting of results in terms of clinical relevance is sparsely used across trials [1]. We confirm the preliminary results published by Van Tulder et al focused on exercise therapy for chronic LBP reporting that less than half of studies (39%) with positive conclusions shown clinically important differences [11].…”
Section: Discussionsupporting
confidence: 91%
“…We call for more adherence to reporting of planned sample size including the clinical relevance with the clinical interpretation of the effects. Without the complete information, the reader is unable to fully interpret the results of a study [1]. On one hand, authors have to report all elements used for sample size calculation, including the clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minority (4.2%) of randomized questions explicitly identified the delta value as the MCID with justification. These findings are in line with the limited number of previous studies investigating clinical significance reporting, wherein under-reporting was found [ 13 , 19 , 20 , 28 , 29 ]. Chan et al [ 13 ] found that, among a random sample of 27 RCTs in major medical journals, 20 articles included sample size calculations, 90% of which reported a delta value but only 11% stated that the delta value was chosen to reflect the MCID of the intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Research suggests that RCT authors rely primarily on statistical significance, they do not consistently provide their own interpretation of the clinical importance of results, and they rarely provide sufficient information to enable readers to draw their own conclusions [ 13 , 19 , 20 ]. The degree to which clinical significance has been assessed in the pediatric oncology literature remains unknown.…”
Section: Introductionmentioning
confidence: 99%